(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The best way to present a floating photovoltaic (FPV) system would be to recognize the increasing demand for renewable energy sources and the challenges faced by traditional land-based solar systems, including limited space and the astronomical costs of installation. One of the possible solutions to these problems is FPV systems, which use water surfaces as a place to install solar panels, such as lakes, reservoirs, and ponds. The research paper will help optimize the energy collection process for FPV systems by developing an Improved Perturb and Observe (IP&O) algorithm with a dual-inductor boost converter (DIBC). This is aimed at precise monitoring of the peak power point, particularly under changing environmental conditions. The simulation results of the suggested MPPT approach in MATLAB/Simulink are consistent with those reported in the literature. The findings show that reaction time and overall functionality of the FPV system improved significantly, highlighting the possible benefits of the IP&O algorithm for optimizing the energy output of floating solar arrays compared to the traditional MPPT approach.